An Old Story of My Farming Days Vol. 2 (of 3). : (Ut Mine Stromtid) - Reuter, Fritz, 1810-1874; Macdowall, M. W. (Salt Lake City, UT : Project Gutenberg, 2011)
"An Old Story of My Farming Days Vol. 2 (of 3)" by Fritz Reuter is a novel written in the late 19th century. The story is set in a rural German community and centers around the life and relationships of various characters, especially focusing on the interactions between the young squire Alick von Rambow, his wife Frida, and the local villagers. It explores themes of love, community, and the dynamics of country life, offering a glimpse into the agricultural practices of the time through everyday experiences. At the start of the novel, the scene unfolds in a summer setting where villagers are preparing for the return of the young squire and his wife to their estate. Key characters such as Christian Däsel and Sophia Degel engage in flirtatious banter, illustrating rural romance, while preparations include setting up a triumphal arch and weaving garlands. As the new couple approaches, the excitement among the villagers is palpable, with humorous attempts to make the welcome memorable, such as creating a makeshift flag. The opening gives a taste of the whimsical yet earnest nature of small-town life, hinting at deeper social interactions and the intricacies of rural society that will be explored as the story progresses. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/From_My_Farming_Days
Release date is 2011-04-13
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: Farm life -- Fiction